SAUSSURE’S TREASURE, HUMILIATION AND OTHER (NEO)LIBERAL TROPES - Silva, Daniel do Nascimento e (Revista da Anpoll, 2016)
While driving its stake into the ground of political economy of language, this paper does two spatiotemporal jumps in order to shed some light on how particular liberal – hence politico-economic – ideologies travel. It first goes back a hundred years ago, to Geneva, and pursues a novel reading of Saussure by delineating his liberal picture of language. It then moves to 2013, in Lima, and looks at some possible consequences of Saussure’s inaugural abandonment of social relationships. In addressing a contemporary scene of humiliation – where young indigenous Peruvian Yaqui Quispe is humiliated by Universidad del Pacifico in its reappraisal of her entrance exam – the paper claims that Saussure’s liberal reified view of social relationships is a fiction that most speakers of the world languages cannot afford. This work is licensed under a Creative Commons Attribution 3.0 License.